2008
DOI: 10.1590/s0034-71672008000500015
|View full text |Cite
|
Sign up to set email alerts
|

Utilização de ácidos graxos essenciais no tratamento de feridas

Abstract: In spite of being widely spread throughout Brazil, the use of essential fatty acids (EFA) for wound healing is controversial. This study aimed at identifying and analyzing the available scientific evidence for EFA to be used in the treatment of wounds. This is a descriptive study, carried out through a systematic literature review, concerning the Biblioteca Virtual de Saúde (Health Online Library) and PubMed data bank, from 1970 to 2006. Initially, we identified 503 references. After the relevance tests I and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
7

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 13 publications
1
9
0
7
Order By: Relevance
“…In agreement with a previous review (14) , in general, the methodology of the studies was not clearly described; there was a lack of details regarding how the evaluation of the described variables was conducted as well as the results (mainly in studies involving human beings), and the form of wound treatment was not clearly described or lacked information; for example, regarding the cleansing method, how the dressings were changed, and the secondary coverage used (if any).…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…In agreement with a previous review (14) , in general, the methodology of the studies was not clearly described; there was a lack of details regarding how the evaluation of the described variables was conducted as well as the results (mainly in studies involving human beings), and the form of wound treatment was not clearly described or lacked information; for example, regarding the cleansing method, how the dressings were changed, and the secondary coverage used (if any).…”
Section: Discussionsupporting
confidence: 56%
“…Regarding the use of EFA in wound treatment, a systematic literature review (14) spanning the period from 1970 to 2006 found that, as far as national scientific production is concerned, few publications have been produced. In view of this fact, and considering that EFA is widely used in wound treatment in Brazil, an interest emerged to identify if more national studies regarding this issue have been produced.…”
Section: Introductionmentioning
confidence: 99%
“…Uma revisão sistemática da literatura realizada sobre a utilização do AGE concluiu que a maioria dos estudos ainda se refere a uso em animais com trabalhos de relevância ainda escassos. Seu uso, com evidências científicas, ainda sem grande robustez, é indicado para queimaduras, nas manifestações cutâneas de deficiência sistêmica desses ácidos e para o tratamento de ferida cirúrgica aberta infectada (19) . Vários fatores podem interferir na escolha adequada da cobertura, dentre elas, a falta de conhecimento dos profissionais, restrições impostas pela equipe médica, a existência de programas locais ou regionais com suas próprias recomendações, uso de diretrizes para o tratamento de feridas, além dos fatores relacionados ao reembolso financeiro pelos planos de saúde (13) .…”
Section: Discussionunclassified
“…Additionally, fatty acids are important modulators of cell signaling for calcium (Soldati et al 2002) and protein kinase C (May and Calder 1993), and they are precursors of lipid mediators such as prostaglandins, thromboxanes and leukotrienes, that stimulate blood vessel constriction and platelet aggregation (O'Shea et al 2004). Fatty acids also accelerate tissue granulation by leukocyte stimuli (Silva et al 2002;Magalhães et al 2008;Manhezi et al 2008), and they are also precursors of arachidonic acid, which induces gene expression in B lymphocytes. These cells are directly involved in repair of damaged tissues (Verlengia et al 2003).…”
Section: Discussionmentioning
confidence: 99%